Conexões entre o desenvolvimento cognitivo e o musical: estudo comparativo entre apreciação musical direcionada e não direcionada de crianças de sete a dez anos em escola regular - Karla Jaber Barbosa (2009)
This piece of research focuses on the study of cognitive-musical development of seven to ten years old children, students at 2nd to 5th grades of Brazilian basic school. Jean Piagets (1964; 1966) theory of cognitive development and Keith Swanwicks Spiral Theory of Musical Development and Vygotskys contributions about this zone of proximal development. The study investigated theoretical connections between Piagets view of the Concrete Operational Period and the Vernacular and SpeculativeSpiral levels as proposed by Swanwick, through the audience-listening modality of musical behavior. Although the Spiral Theory is a robust contribution about musical development, it does not explain the cognitive processes that underlie the transition between levels of development.It consists of a comparative study between two conditions: independent audiencelistening activity and directed audience-listening activity, after the teachers interference. The observation of students performance, the study of the Concrete Operational Period and the detailing of cognitive processes, the data show that the acquisition of conservation and reversibility may promote the transition from Vernacular to Speculative levels. These data also indicate that children achieved higher levels of musical understanding after the teachers interference. Keywords: audience-listening, musical development, conservation, zone of proximal development, Spiral Theory.